Pelatihan Digital Marketing RT.06 Kelurahan Graha Indah, Kecamatan Balikpapan Utara - Naretha, Naretha Kawadha Pasemah Gumay; Sartika, Widya Sartika; Prabowo, I Putu Deny Arthawan Sugih Prabowo; Syaputra, Eko Agung Syaputra; Wibowo, Darrell Rajendra Wibowo; Ramadhanti, Aulia Azizah Ramadhanti; Hijrah, Dinda Sa’adatul Hijrah; Wibowo, Faqih Putra Wibowo; Riyadi, Andrew Arief Riyadi; Nurmana, Fikrie Ari Nurmana; Kelana, Muhammad Raihan Wirayudra Kelana (Apik Cahaya Ilmu, 2024)
Digital Marketing Training in RT.06 Graha Indah Village, North Balikpapan District is a community service activity carried out by lecturers and students. This activity aims to provide practical experience to lecturers and students in developing and implementing effective digital marketing strategies in helping the MSME community in the RT 06 area. Graha Indah Village, North Balikpapan District in maximizing product potential and improving their ability to market their products. Lecturers and students provide training using the Case Based Learning (CBL) method so that training participants can directly apply the learning outcomes to their respective products. Based on the data from the questionnaire given before and after the training, there was an increase in the ability of training participants to market their products. Keywords: copywriting, content strategy, digital marketing, sales and marketing